Celebrating Ann Wilcock: A call to action. Issue 1 (2nd January 2020) - Hocking, Clare; Townsend, Liz
ABSTRACT: Dr. Ann Allart Wilcock (née Ellison) made outstanding contributions to occupational science, as a new discipline, and to the century old profession of occupational therapy. In celebrating that legacy, we are calling for action with research advancing three important 'themes' with global relevance that we see in Wilcock's work. First, she was a world pioneer in expanding awareness and empirical knowledge of the occupational nature of humans, that is to say knowledge of human occupation as "innate and related to health and survival" (Wilcock, 1993, p. 17). Second, Wilcock bridged the gap between human occupation, as an almost invisible aspect of daily lifestyles, and population health. Third, she emphasized humans' need to understand and work toward the ideal of an occupationally just world.